Upaya Perencanaan dan Pengembangan SDM Guna Meningkatkan Produktivitas dan Efektivitas pada Perusahaan Suzuki Cabang Sutomo - Jihan Atifa; Tri Yoma Elsa; Viona Billa Ababil; Yuliana Fransiska; Ramdani Bayu Putra (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the efforts in human resource (HR) planning and development to enhance productivity and work effectiveness at Suzuki Company, Sutomo Branch. Well-structured HR planning and competency development strategies are considered crucial factors in supporting the achievement of operational targets and improving overall company performance. The research adopts a descriptive qualitative approach with data collected through interviews, observations, and document analysis. The findings indicate that continuous training programs, regular performance evaluations, and structured career management have a positive impact on employee motivation and operational efficiency. Therefore, focused and consistent HR planning and development are essential strategies for creating competitive advantages amidst the increasingly intense competition in the automotive industry.